2018
DOI: 10.1080/2331205x.2018.1463894
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-perceived risk for common conditions

Abstract: Background:Accurate awareness of common disease risk is necessary to promote healthy lifestyles and to prevent unnecessary anxiety and evaluation. Our objective is to identify characteristics of patients who do not accurately perceive their risk of developing coronary heart disease (CHD), diabetes (DM), breast cancer (BC) and colorectal cancer (CRC).Methods:Using personalized disease risk reports and risk perception surveys, subjects (n = 4703) were classified as high or low/average risk and high or low/averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…Our findings are in accordance with previous researches in various conditions, which reported that patients do not correctly perceive their own risk irrespective of their actual risk [48]. Among patients at high risk for developing CVD, 57% underestimated their risk, and a very similar proportion of low/moderate-risk patients (56%) overestimated the risk [48]. In a Brazilian study, asymptomatic subjects with higher CVD risk according to the Framingham risk score or the lifetime risk score were more likely to underestimate their risk than subjects at intermediate risk [51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in accordance with previous researches in various conditions, which reported that patients do not correctly perceive their own risk irrespective of their actual risk [48]. Among patients at high risk for developing CVD, 57% underestimated their risk, and a very similar proportion of low/moderate-risk patients (56%) overestimated the risk [48]. In a Brazilian study, asymptomatic subjects with higher CVD risk according to the Framingham risk score or the lifetime risk score were more likely to underestimate their risk than subjects at intermediate risk [51].…”
Section: Discussionsupporting
confidence: 93%
“…Patients at high or very high actual CVD risk tended to underestimate their risk. Our findings are in accordance with previous researches in various conditions, which reported that patients do not correctly perceive their own risk irrespective of their actual risk [48]. Among patients at high risk for developing CVD, 57% underestimated their risk, and a very similar proportion of low/moderate-risk patients (56%) overestimated the risk [48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An accurate awareness of personal risk is an important component in risk-prevention behaviours (Brawarsky et al, 2018). However, there is often a large 'perception gap' between perceived and objectively calculated risks (Cainzos-Achirica & Blaha, 2015).…”
Section: Perceptions Of Riskmentioning
confidence: 99%
“…Despite extensive efforts to inform parents of their multiple islet autoantibody positive child's high T1D risk, 21% of mothers of these children in stage 1 of T1D underestimated their child's T1D risk 19 . Risk communication is very challenging and the literature is replete with examples of risk underestimation in T1D as well as other diseases 28‐30 . These findings suggest the need to develop better risk communication and intervention tools for targeted populations who have difficulty understanding this complex concept.…”
Section: Discussionmentioning
confidence: 99%